Acute Effect of High Fat Intake on Urinary Acidification Parameters - Alireza Zomorodian; Xilong Li; John Poindexter; Naim M. Maalouf; Orson W. Moe; Khashayar Sakhaee (Kidney International Reports, 2025)
Introduction: The prevalence of uric acid nephrolithiasis has increased contemporaneously with obesity. The key pathogenic factor in uric acid nephrolithiasis is acidic urine pH (UpH), which partially results from reduced buffering of H+ by ammonia (NH3). Renal proximal tubule ammoniagenesis from amino acids generates adenosine triphosphate and NH3. We tested whether the provision of free fatty acids (FFAs) as an alternative nonnitrogen energy source (substrate switch) reduces renal ammoniagenesis in uric acid stone formers (UASFs) compared with non–stone forming controls (Ctrls). Methods: Seven UASFs and 8 Ctrls were equilibrated on a fixed metabolic diet for 4 days. After sampling fasting urine and blood, the subjects received oral fat load over 10 hours, with blood and urine samples collected every 2 hours. Results: Both groups exhibited significant and similar increases in serum FFAs. UpH progressively decreased from 6.6 to 5.6 in the Ctrl group over 10 hours (P-value for trend < 0.001), whereas UpH started lower (5.3) in the UASF group and remained unchanged. The fraction of net acid excretion (NAE) in the form of ammonium (NH4+) (NH4+-to-NAE ratio) was lower at baseline in the UASF group than in the Ctrl group (P = 0.002) and decreased significantly in both groups during the 10-hour fat load. Conclusion: In conclusion, Ctrls showed reduced NH4+ excretion with an acute fat load, consistent with substrate switch. However, UASFs demonstrated a chronic stable NH4+ excretion defect consistent with lipotoxic impairment of proximal tubule function. Although dietary fat affects ammoniagenesis or excretion, dietary fat restriction alone is likely insufficient for managing the aciduria in UASFs.